2018
DOI: 10.1080/07391102.2018.1465852
|View full text |Cite
|
Sign up to set email alerts
|

Identification of some novel pyrazolo[1,5-a]pyrimidine derivatives as InhA inhibitors through pharmacophore-based virtual screening and molecular docking

Abstract: The InhA inhibitors play key role in mycolic acid synthesis by preventing the fatty acid biosynthesis pathway. In this present article, Pharmacophore modelling and molecular docking study followed by in silico virtual screening could be considered as effective strategy to identify newer enoyl-ACP reductase inhibitors. Pyrrolidine carboxamide derivatives were opted to generate pharmacophore models using HypoGen algorithm in Discovery studio 2.1. Further it was employed to screen Zinc and Minimaybridge databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The average RMSD descriptor of all the docked compounds were calculated to corroborate their stability in biological system [ 28 , 29 , 30 ]. As the justified threshold for RMSD calculation is 2 Å, its mean average RMSD value of all the complexes less than this threshold provides us with the proof that our docking process is validated, as having RMSD for anti-cancer docking protocol 2.0 Å, for anti-diabetic 1.35 Å and for anti-oxidant 0.71 Å [ 31 , 32 , 33 , 34 ]. Redocked ligand and co-crystal structure’s native ligand superimposed images are shown in Figure 13 A–C [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 90%
“…The average RMSD descriptor of all the docked compounds were calculated to corroborate their stability in biological system [ 28 , 29 , 30 ]. As the justified threshold for RMSD calculation is 2 Å, its mean average RMSD value of all the complexes less than this threshold provides us with the proof that our docking process is validated, as having RMSD for anti-cancer docking protocol 2.0 Å, for anti-diabetic 1.35 Å and for anti-oxidant 0.71 Å [ 31 , 32 , 33 , 34 ]. Redocked ligand and co-crystal structure’s native ligand superimposed images are shown in Figure 13 A–C [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 90%
“…Pertersen et al [ 35 ] have used the virtual screening techniques to identify novel inhibitor for M. tuberculosis 3-dehydroquinate. Similarly, another study has employed pharmacophore-based virtual screening to identify the pyrazolo [1,5- a ] pyrimidine derivatives against InhA of M. tuberculosis [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking studies buoyed that selected compounds can work as a lead inhibitor of bacterial DNA synthesis and membrane permeation due to conformational fitting in the active site of the targeted protein, especially compound pyrrolo (2,1-F) pyrazine-1,4dione,2,3,6,7,8,8A-hexahydro-3-(phenylmethyl)-(14705-60-3), which has a greater binding affinity (−6.4 kcal/mol) compared to antibiotic Ertapenem (−6.1 kcal/mol). While there are many in silico models and detection of compounds against MDR and XDR tuberculosis [35,36], limited studies have reported active compounds and in silico docking against XDR A. baumannii. Therefore, to the best of our knowledge, this is the first report on the identification of DKP against XDR A. baumannii.…”
Section: Discussionmentioning
confidence: 99%